If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3 + 6x = x + 7 Reorder the terms: -3 + 6x = 7 + x Solving -3 + 6x = 7 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -3 + 6x + -1x = 7 + x + -1x Combine like terms: 6x + -1x = 5x -3 + 5x = 7 + x + -1x Combine like terms: x + -1x = 0 -3 + 5x = 7 + 0 -3 + 5x = 7 Add '3' to each side of the equation. -3 + 3 + 5x = 7 + 3 Combine like terms: -3 + 3 = 0 0 + 5x = 7 + 3 5x = 7 + 3 Combine like terms: 7 + 3 = 10 5x = 10 Divide each side by '5'. x = 2 Simplifying x = 2
| z+3.6=2.5 | | -0.24p+1.602=1.29 | | 1X+4Y=58 | | -5x-10=-3+2x | | 7(n-4)-(6-3n)=9n | | 0,001*0,001x=1/8 | | 2+3x=-5x-6 | | 2x-5=-2+x | | H=0.001x^2-X+27 | | 12h=72 | | (x+4)+(x+2)+(x+5)=2(x+1)+2(x+3) | | 90m^2+21mn-6n^2=0 | | T-75H=735 | | 9x+7-7x=4+x+5 | | -2=6+2x | | -20=b-5 | | 8-n=6+4n | | -9+7m=1+5m | | (m+2)(m-2)=0 | | 3(5-q)+6=9 | | 5(x+2)-(2x-7)= | | 10g=1100 | | x+4+x+2+x+5=2(x+1)+2(x+3) | | 10=1100 | | 3x-6=-14-7+6x+6 | | m^2-6m-33=-6 | | 5x-2=2x-35 | | 4x=38-2x+8 | | 5n^2-50n+105= | | Gsquared+3g=70 | | -10(-m)= | | b+3a=21 |